Features of ultrasound of endometrial pathological conditions in breast cancer patients receiving tamoxifen: a review of literature - M. A. Chekalova; M. I. Borisova (ABV-press, 2020)
The article examines the possibilities and features of ultrasound in the diagnosis of endometrial pathological conditions on the background of taking tamoxifen in women diagnosed with breast cancer based on data obtained from studying the sources of domestic and foreign literature from 1994 to 2018.